Tuning the porosity through interpenetration of azobenzene-4, 4′-dicarboxylate-based metal–organic frameworks1. Issue 40 (28th October 2015) - Fernández, Belén; Seco, José Manuel; Cepeda, Javier; Calahorro, Antonio J.; Rodríguez-Diéguez, Antonio
<x xml:space="preserve">Abstract</x> Pore size is tuned in a series of azobenzene-4, 4′-dicarboxylate/3, 6-bis(4-pyridyl)-1, 2, 4, 5-tetrazine/Zn or Cd based MOFs through a variable interpenetration degree. These structural features promote subtle shifts in the blue emission of the compounds.